Povazhenny, Chto Naryazhenny. In Search of the lnternal Form - Shteingold, Anzhelika (Respectus Philologicus, 2005)
The present article, an attempt ata reconstruction of the original internal form of the “non-transparent”paroemiac expression Povazhenny, chtonaryazhenny (variants: poryazhenny, zaporyazhenny), which is found in Russian 19-th century fiction describing folk life and customs, is made. The author of the article confirms the connection of the substantiated adjective povazhenny‘attracted by the means of sorcery’, with a proto-Slavic verb *vaditi l ‘to seduce, to accustom (to evil)’ defined by l. P. Petleva, which, in its own tum, is derived from a proto-Slavic root *ved-/*vod- ( < *y.edh/*uodh-) ‘to lead, to conduct’. The meaning ‘to seduce, to accustom (to evil)’ of this verb developed from the intermediate semantic link ‘make somebody lead you’, which is confirmed by the formal features of *vaditi I as the causative regarding *voditi. For *vaditi l ritual semantic specialisation, connection with magic and sorcery were indicated quite early. Lexeme naryazhenny, correlating with the vast circle of regional single-rooted derivatives containing references to a wedding ritual, means ‘intended to be a husband by contract’. The research of contextual usages of expression suzheny-ryazheny and the like confirms this semantic interpretation of the second component of paroemia. As a result, the mentioned paroemia obtains the following historical interpretations: “Charmed fiance is a candidate for a husband as undeniable as the one, who has already been approved by the society (family) for the given fiancee”.